Morphological features of vascular lesions of the microvasculature in sepsis - V. S. Chirskij; E. A. Andreeva; A. K. Yuzvinkevich (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2021)
Introduction.Sepsis is a public health priority due to its high incidence and mortality. There are no clear criteria for assessing the vessels of the microvasculature in the pathological diagnosis of septic condition.The objective of the work was to characterize changes in the vessels of the microvasculature with different morphological variants of sepsis.Methods and materials. We analyzed 93 cases of death with a clinical diagnosis of sepsis. A study was made of pathomorphological signs of microcirculatory disorders, organ cell damage, and the presence of inflammatory infiltrates.Results. In the course of the study, it was found that the morphological manifestations of sepsis, in addition to purulent metastasis of various degrees of severity, are signs of damage to microvessels, such as the expression of adhesive molecules by the endotheliocytes, their desquamation, leukocyte stasis, marginal standing and output of single leukocytes beyond the vessels, fibrin and hyaline microthrombi as a manifestation of DIC syndrome.Conclusion. Regardless of the severity of the purulent metastatic process, septic lesions are characterized by the same changes in the microvasculature, expressed in increased expression of adhesive molecules by the endotheliocytes (ICAM-1), desquamation of endotheliocytes (51 %), marginal standing of leukocytes (38 %), the output of single leukocytes beyond the vessels (21 %), leukocyte stasis (55 %), the formation of fibrin and hyaline microtrombi (45 %), the sludge phenomenon (91 %), diapedetic hemorrhage in the tissues (72 %), which indicate a leading role in microcirculation disorders and, correspondingly, the formation of multiple organ failure during sepsis of secondary microvascular damage. With septicopyemia, bacterial dissemination leads not only to primary damage of the walls of blood vessels, but also to activation of their secondary lesions, as evidenced by the revealed relationship between an increase in the severity of purulent metastasis and an increase in the number of microtrombiin blood vessels, the frequency of detection of diapedetic hemorrhages in brain tissue, and hyaline membranes in alveoli of the lungs, leukocyte stasis in the vessels of the myocardium and kidneys, necrosis of the vascular loops of the glomeruli of the kidneys.